Effect of Cerebral Ischemic Strokes in Different Cerebral Artery Regions on Left Ventricular Function - Zheng, Li-Juan; Lin, Xin; Xue, Yun-Jing (Frontiers in Cardiovascular Medicine, 2022)
Objectives: The relationship between cerebral ischemic stroke and left ventricular function evaluated by echocardiography has been emphasized. Whether lesions in different cerebral artery regions would result in left ventricular dysfunction remains uncertain. Methods: Patients were divided into middle cerebral artery (MCA) (n = 79), posterior cerebral artery (PCA) (n = 64), basilar artery (BA) regions (n = 66) and no-ischemic stroke group (n=209). We retrospectively collected demographic characteristics, hematologic parameters, and electrocardiogram results, and a comparison of echocardiographic parameters was performed to determine the relationship between ischemic stroke and left ventricular function. Results: A total of 418 patients were included. Demographic characteristics did not significantly differ between the ischemic stroke and non-ischemic stroke groups, except for a history of drinking (P < 0.001). Homocysteine levels in the MCA group were higher than those in the PCA and BA groups (P < 0.05). Highly sensitive C-reactive protein was higher in the ischemic stroke group than in the non-ischemic stroke one (P = 0.001). A higher incidence of ST-T changes in the electrocardiogram and lower levels of potassium and magnesium in the ischemic stroke group were found. Significant differences in diastolic function between groups were noted, and the early mitral inflow velocity, annular early diastolic velocity, and ratio between mitral annular early diastolic velocity and mitral annulus atrial inflow velocity in the MCA group were lower than those in the BA group (P < 0.05). Conclusions: Ischemic strokes exhibited a negative effect on left ventricular diastolic function by echocardiography, especially in MCA region infarcts. These results are of great importance for neurologists as they highlight the need for left ventricular function evaluation after stroke to regulate therapy strategies in time.